Analisis Biodiesel Sebagai Aditif Bahan Bakar Diesel Terhadap Kinerja dan Konsumsi Bahan Bakar Mesin Pembangkit Listrik - Prasetiyo, Dani Hari Tunggal; Sidartawan, Robertus; Sanata, Andi; Yudhistiro, Danang; Nisak, Rima Zidni Karimatan (TURBO [Tulisan Riset Berbasis Online], 2024)
Research on the use of biodiesel as renewable energy must continue to be carried out as an effort to reduce dependence on fossil energy. This research method was carried out using biodiesel from used cooking oil as an additive to fossil diesel fuel (dexlite). The fuel was tested on a diesel engine as a power generator accompanied by variations in power loading (load). The composition of biodiesel as an additive was (10, 20 and 30)% of fossil diesel fuel, while the power load used during testing was 100 to 700 watts. Testing was carried out to determine the performance and fuel consumption of a diesel engine as a power generator. The test results showed that the highest effective power value was in the D0 composition with a value of 278.18 watts with a power load of 700 watts, while the highest torque value was in the D0 fuel composition of 2.23 Nm at a power load of 700 watts. The lowest fuel consumption was in the D70BIO30 fuel composition of 114.25 seconds at a power load of 100 watts.